Molecular characterization of humic-like substances (HULIS) in atmospheric particles (PM2.5) in offshore Eastern China Sea (OECS) using solid-phase extraction coupled with ESI FT-ICR MS. (1st February 2023) - Sun, Hao; Wu, Zilan; Kang, Xinyuan; Zhu, Chao; Yu, Limin; Li, Ru; Lin, Zhongsheng; Chen, Jianmin
Abstract: Humic-like substances (HULIS) are organic macromolecular compounds (water-soluble brown carbon) that have an important effect on climate change due to their strong light absorption. However, the molecular composition of HULIS in atmospheric particles in the offshore Eastern China Sea (OECS) has scarcely been investigated. In this study, solid-phase extraction (SPE) was performed to collect HULIS from water extracts. The molecular compositions of samples were characterized by negative-ion electrospray ionization (ESI) Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR MS). A total of 1197–1828 molecular formulas of HULIS were identified in collected samples, and three of them with higher intensities near Shanghai city, Zhejiang province, and Fujian province were discussed in detail. The identified molecular formulas were classified into four major subgroups, including CHO, CHNO, CHOS, and CHNOS compounds. S-containing formulas (CHOS and CHNOS) represented the dominant components (21.0–76.7% relative abundance), followed by CHO (16.5–64.3%), while CHNO compounds constituted 6.1–18.1% of the identified formulas. High fractions of CHO formulas were found in the list of α-pinene ozonolysis yields and S-containing formulas with olefinic structures were abundant in atmospheric particles, suggesting enhanced SOA formation. The samples had a relative abundance-weighted average O/C of 0.25–0.67 and a double bond equivalent of 3.49–4.96. Most identified formulas (>89%) were assigned to aliphatic and olefinic species. The CHNO and S-containing formulas identified in the samples were primarily contributed by –ONO2 functional groups and organosulfates. Biogenic volatile organic compounds (α-pinene or monoterpene) were the dominant precursors of HULIS in the samples. Lignin-like species (41–46%) and protein/amino sugars (28–30%) were the major species among substance classes. The results provide an improved understanding of the molecular composition of HULIS in the Eastern China Sea. Highlights: The molecular composition of humic-like substances (HULIS) was investigated in OECS. Most identified compounds were assigned to aliphatic and olefinic species. HULIS in marine aerosols were mainly derived from biogenic sources rather than anthropogenic sources.